EFFECT OF STAGGARED PLANTING ON THE SEASONAL ABUNDANCE OF DIAMONDBACK MOTH (PLUTELLA XYLOSTELLA LINN) ON CABBAGE UNDER NORTH EASTERN HILL ZONE, IMPHAL - H.VANLALDIKI,; SINGH , M. PREMJIT; LALRINSANGA, ROBERT (The Bioscan, 2013)
The experiment was attempted during the rabi season of 2009-10and 2010-11 to study the effect of staggered planting on seasonal incidence vis-à-vis peak period of incidence of diamondback moth, Plutella xylostella (Linn.). Results revealed that in both the years, the larvae of diamondback moth first appeared at the end of January (0.20 and 0.15/plant), increased gradually and reached its peak by the end of March with a population (12.05 and 11.20/plant) during the two seasons respectively. The larval population declined (2.20 and 0.60/ plant) by the second week of April in both the years. The correlation studies indicated a significant positive correlation between larval population of diamondback moth and max. and min. temperature with an exception to the second year max. temperature, which showed a non-significant interaction. During 2009-10, the relative humidity (R.H), total rainfall and bright sunshine hours (BSSH) had negative correlation, whereas in the second year (2010-2011), R.H and rainfall had positive relation with the larval population of diamondback moth. There was a marked variation of diamondback moth incidence in different dates of planting. The result showed that early planted crop (15th Nov.) harbored least number of the target pest (0.06/plant) with highest yield (20.80t/ha) whereas late planting (14th Jan.) resulted in highest population (3.37 /plant) with the lowest yield of 6.15t/ha and devoid of any marketable heads.